(3JPcQI Chdi GdCdHGH hGdLGeY ddYLH GdYLGHs - (3OGhO Hf YeQ GdHUjQ GdCfWGcj, J (B1008 (3g` s
(3ChdgG (B:s
(3SHMGf eHOY ehGO GdcGFfGJ HdG eKGd SHb hHYO aJaGVd GaQGO GdfhY GdEfSGfi Ydi HYVgG HYVkG CXgQ ef Cf jMJGL Edi Odjd s
(3BNQgG (B:s
(3hGdMPQ ef ONGf PQb GdMeGe hfHZi Cf Jfbd cd YGe eQI aGaYd agPG LejY eG JOYhG GdMGLg Edjg ef gPg GdUfGYI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B386s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs